2004
DOI: 10.1016/j.virol.2003.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Mode of transgene expression after fusion to early or late viral genes of a conditionally replicating adenovirus via an optimized internal ribosome entry site in vitro and in vivo

Abstract: The expression of therapeutic genes by oncolytic viruses is a promising strategy to improve viral oncolysis, to augment gene transfer compared with a nonreplicating adenoviral vector, or to combine virotherapy and gene therapy. Both the mode of transgene expression and the locale of transgene insertion into the virus genome critically determine the efficacy of this approach. We report here on the properties of oncolytic adenoviruses which contain the luciferase cDNA fused via an optimized internal ribosome ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…Simultaneously, the SOCS3 gene was fused with the cpp gene (cell-penetrating peptide), which has the capacity to deliver peptides, proteins, and oligonucleotides into intact cells (22,23). In addition, in the backbone of the adenovector, expression of the SOCS gene was controlled by an endogenous adenoviral major late promoter (MLP) which restricts SOCS3 expression within the tumor microenvironment due to tumor-specific viral replication (24). A previous study showed that this recombination manipulation of the oncolytic vector did not affect replication of the virus (10).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the SOCS3 gene was fused with the cpp gene (cell-penetrating peptide), which has the capacity to deliver peptides, proteins, and oligonucleotides into intact cells (22,23). In addition, in the backbone of the adenovector, expression of the SOCS gene was controlled by an endogenous adenoviral major late promoter (MLP) which restricts SOCS3 expression within the tumor microenvironment due to tumor-specific viral replication (24). A previous study showed that this recombination manipulation of the oncolytic vector did not affect replication of the virus (10).…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of mRNA copy numbers was performed by real-time PCR as previously described. 34 For the assay, known amount of template DNA of pTG3602 (10 8 , 10…”
Section: Quantification Of E1a and E4 Mrnamentioning
confidence: 99%
“…IRESs are highly structured viral sequences that facilitate bicistronic gene expression by internal translation initiation in addition to translation initiation at the 5' end of mRNAs. For example, the approximately 600-bp encephalomyocarditis virus (EMCV) IRES has been used for transgene insertion into both early and late Ad transcription units (Sauthoff et al, 2002;Rivera et al, 2004). Alternative splicing is widely utilized by Ads as a mechanism for expression of multiple proteins from one transcription unit.…”
Section: Introductionmentioning
confidence: 99%